Ragam dan Fungsi Plesetan pada Jenama Kaos Nyenyes di Palembang - Yeni Ernawati; Dita Aprilia Zahara (STIKes Ibnu Sina Ajibarang, 2024)
Through this research, the researcher describes the variety and function of pun (Plesetan) on Kaos Nyenyes brand. This study uses a descriptive qualitative method with the research object being the design of the pun text found on Nyenyes shirts. Data collection was carried out using documents. The data analysis technique used is the basic distribution technique, through four stages: collecting data, identifying data, classifying data, and analyzing data based on the variety and function of the plesetan. From the data analysis results, there are 6 types of plesetan on the Kaos Nyenyes brand, namely phonological puns, graphic puns, phrase puns (word groups), sentence puns (expressions), discursive puns, and portmanteau words puns. Puns on Kaos Nyenyes serves functions of creativity, prestige, humor communication, satire, and self-reflection in advantageous situations. Additionally, puns discourse also has another function, which is marketing to attract public interest to purchase Nyenyes shirts in Palembang city.